2010
DOI: 10.1002/jbm.a.32884
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of MMP sensitive high‐molecular weight HA‐based hydrogels for bone tissue engineering

Abstract: Hyaluronic acid (170 kDa)-based hydrogel was synthesized using acrylated hyaluronic acid (HA) and matrix metalloproteinase (MMP) sensitive HA-based hydrogels were then prepared by conjugation with two different peptides: cell adhesion peptides containing integrin-binding domains (Arg-Gly-Asp: RGD) and a cross-linker with MMP degradable peptides to mimic the remodeling characteristics of natural extracellular matrices by cell-derived MMPs. Mechanical properties of these hydrogels were evaluated with different w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 43 publications
2
48
0
Order By: Relevance
“…On the contrary, there is also abundant evidence based on animal studies that ex vivoexpanded hMSCs improve injury repair in a range of tissue, including bone or neuron, after in vivo transplantation into animals without any notable inflammation. [9][10][11] Consistently, our previous studies have shown enhanced bone regeneration in a rat calvarial defect model using BM-hMSCs delivered by a hydrogel carrier. 10,11 There is no doubt that for direct orthotopic applications, it would be helpful to use appropriate scaffolds to hold cells in place and support their differentiation.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…On the contrary, there is also abundant evidence based on animal studies that ex vivoexpanded hMSCs improve injury repair in a range of tissue, including bone or neuron, after in vivo transplantation into animals without any notable inflammation. [9][10][11] Consistently, our previous studies have shown enhanced bone regeneration in a rat calvarial defect model using BM-hMSCs delivered by a hydrogel carrier. 10,11 There is no doubt that for direct orthotopic applications, it would be helpful to use appropriate scaffolds to hold cells in place and support their differentiation.…”
supporting
confidence: 55%
“…[9][10][11] Consistently, our previous studies have shown enhanced bone regeneration in a rat calvarial defect model using BM-hMSCs delivered by a hydrogel carrier. 10,11 There is no doubt that for direct orthotopic applications, it would be helpful to use appropriate scaffolds to hold cells in place and support their differentiation. 7 However, in DO studies, MSCs have been delivered using direct injection either with an injectable gel 15 or recently by suspension in a saline solution 17,29 into the osteotomy site, probably due to the anatomical and pathological characteristics of DO.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Numerous studies have shown that codelivery of growth factors and MSCs both in vitro and in vivo enables regenerative potential more efficiently than MSCs alone. 6,21,22 When cotransplanted with MSCs and growth factors, a collagen sponge is preferred. This is especially the case when BMP-2 is used as a growth factor; collagen sponges have characteristics that allow for sustained release of BMP-2 in addition to their biocompatible, osteoconductive properties.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of growth-promotive factors is used to stimulate the differentiation of transplanted MSCs and enhance their activity as well as recruit undifferentiated osteoprogenitor cells into the vehicle. Until now, numerous investigations have shown the regenerative potential of growth factors and MSC codelivery in vitro and in vivo [Kim et al, 2007[Kim et al, , 2010Terella et al, 2010]; however, the synergistic effect of growth factors for a significant increase in bone formation is still unclear. Codelivery of MSCs with other cell types, such as endothelial cells and osteoblasts, may be another interesting option for increasing the osteogenic efficacy.…”
Section: Codelivery Of Mscs With Other Cell Types or Growth Factorsmentioning
confidence: 99%